MANAGEMENT OF URINARY CALCULUS WITH HERBAL PREPARATION (MORINGA OLEIFERA AND TRIBULUS TERRESTRIS) - Vishal Khanna; Anjali Sharma (AYUSHDHARA, 2021)
Urinary stones are a common disease that remains a significant health problem. It carries significant morbidity and imposes tremendous financial burden on healthcare system. Urolithiasis affects up to 5% of the population, with a recurrence rate of 50 to 80%. Males are more frequently affected than the females. Management includes both medicinal and surgical treatment which depends on size, type and location of stone. Larger stones which fail to pass through urinary system, needs treated by surgical interventional such as Extracorporeal shock wave lithotripsy (ESWL), Ureteroscopy, and Percutaneous Nephrolithotomy etc. For prevention and recurrence of stone, many herbal medicines have been used traditionally which are believed to cause the disintegration, dissolution and dislodgement and expulsion of urinary stones. In Ayurveda, there are references and comprehensive description of various herbal drugs regarding their anti-lithaitic properties. Role of Moringa oleifera (Shigru mool) and Tribulus terrestris (Gokshura phala) has been highly mentioned. In the present study, a total of 30 patients of Urolithiasis (Mutrashmari) with stone size up to 12mm were selected and all patients were randomly assigned to receive the designed herbal treatment i.e., decoction of Moringa oleifera and Tribulus terrestris for a maximum of 60 days. The study concluded that the herbal formulation is found significant in improving the symptoms of Urolithiasis in all patients and stones in 11 patients were also expelled out.